2018
DOI: 10.1080/17520843.2018.1534873
|View full text |Cite
|
Sign up to set email alerts
|

Bangladesh’s trade partners and the J-curve: an asymmetry analysis

Abstract: Separating currency appreciations from depreciations and using nonlinear models in recent literature have improved discovering significant link between the trade balance and the exchange rate. We add to this growing literature by considering the experience of Bangladesh with 11 trading partners. When a linear model was used, support for the J-curve effect was present only with one small partner. However, when a nonlinear model was used, support increased to three countries including the largest partner, the U.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Thus, their findings strongly indicate that NARDL is more superior than the conventional ARDL method in providing support for J-curve phenomenon. Many other papers reported the same results, which can be instanced as Bahmani-Oskooee and Baek (2018) , Bahmani-Oskooee et al., 2018a , Bahmani-Oskooee et al., 2018b , Ari et al. (2019) , Bahmani-Oskooee and Fariditavana, 2020 , Bahmani-Oskooee et al., 2019a , Bahmani-Oskooee et al., 2019b , Bahmani-Oskooee and Nasir (2019) , Bahmani-Oskooee and Fariditavana (2020) , and Bahmani-Oskooee and Nouira (2020) .…”
Section: Literature Reviewmentioning
confidence: 58%
See 2 more Smart Citations
“…Thus, their findings strongly indicate that NARDL is more superior than the conventional ARDL method in providing support for J-curve phenomenon. Many other papers reported the same results, which can be instanced as Bahmani-Oskooee and Baek (2018) , Bahmani-Oskooee et al., 2018a , Bahmani-Oskooee et al., 2018b , Ari et al. (2019) , Bahmani-Oskooee and Fariditavana, 2020 , Bahmani-Oskooee et al., 2019a , Bahmani-Oskooee et al., 2019b , Bahmani-Oskooee and Nasir (2019) , Bahmani-Oskooee and Fariditavana (2020) , and Bahmani-Oskooee and Nouira (2020) .…”
Section: Literature Reviewmentioning
confidence: 58%
“…The cases with J-curve effect are summarized in Table 1 . Regarding the bilateral exchange rate model, the J-curve effect caused by POS (i.e., depreciation of VND) is witnessed in the cases of France, Greece, Portugal, Romania, Spain and Sweden, as evidenced by the significant negative or insignificant short-run coefficients of POS variables combined with their corresponding positive long-run ones ( Rose and Yellen, 1989 ; Bahmani-Oskooee and Fariditavana, 2015 ; Bahmani-Oskooee et al., 2018a , Bahmani-Oskooee et al., 2018b ). Among the aforementioned countries, France is the third biggest EU trading partner of Vietnam during the 2000Q1–2018Q1 period.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, in rather later evidence on the Austrian economy Darne and Hoarau (2007) could not find the tendency of PPP to hold in Australia. In the recent evidence from bilateral trade balances of Bangladesh, Bahmani-Oskooee et al (2017) also reported mixed results on the presence of the J-curve, though there was strong support for the presence of J-curve in the trade balance with the US. Similarly, in the most recent evidence, focussing on US–Mexico bilateral trade, Bahmani-Oskooee et al (2018) reported significant evidence of short-run and long-run asymmetric effects of exchange rate changes.…”
Section: Nexus Exchange Rate Misalignment and Trade Imbalancementioning
confidence: 99%
“…9. Initial deterioration and then long-term improvement of trade balance due to exchange rate depreciation forming a J-curve response (please see Bahmani-Oskooee and Ratha, 2004; Bahmani-Oskooee and Hegerty, 2010; Bahmani-Oskooee et al , 2013 or most recently Bahmani-Oskooee and Saha, 2017; Bahmani-Oskooee et al , 2017). …”
Section: Notesmentioning
confidence: 99%